Mechanism of Auxin-induced Ethylene Production - Kang, Bin G. (1971)
Indoleacetic acid-induced ethylene production and growth in excised segments of etiolated pea shoots (Pisum sativum L. var. Alaska) parallels the free indoleacetic acid level in the tissue which in turn depends upon the rate of indoleacetic acid conjugation and decarboxylation. Both ethylene synthesis and growth require the presence of more than a threshold level of free endogenous indoleacetic acid, but in etiolated tissue the rate of ethylene production saturates at a high concentration and the rate of growth at a lower concentration of indoleacetic acid. Auxin stimulation of ethylene synthesis is not mediated by induction of peroxidase; to the contrary, the products of the auxin action which induce growth and ethylene synthesis are highly labile.